2020
DOI: 10.36660/abc.20190296
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da Heroína nos Parâmetros Eletrocardiográficos

Abstract: Resumo Fundamento Atualmente, o vício em heroína é um problema de saúde preocupante, e as informações sobre os efeitos eletrocardiográficos da heroína são limitadas. Objetivos O objetivo do presente estudo é investigar os efeitos da dependência de heroína em parâmetros eletrocardiográficos. Métodos Um total de 136 indivíduos, incluindo 66 indivíduos que fumam heroína como grupo de estudo e 70 indivíduos saudáveis sem dependência … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
(69 reference statements)
0
2
0
1
Order By: Relevance
“…QT interval prolongation was reported in previous studies of addiction population; however, it was usually related to cocaine abuse or concurrent methadone therapy (Demarie et al, 2011). (Yildirim et al, 2020) demonstrated that heroin abuse significantly changed QT interval independent from the effect of adulterants and methadone. Tramadol also is known as an intermediate risk drug for developing long QT interval in high doses (Behzadi et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…QT interval prolongation was reported in previous studies of addiction population; however, it was usually related to cocaine abuse or concurrent methadone therapy (Demarie et al, 2011). (Yildirim et al, 2020) demonstrated that heroin abuse significantly changed QT interval independent from the effect of adulterants and methadone. Tramadol also is known as an intermediate risk drug for developing long QT interval in high doses (Behzadi et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Diacetylmorphine has varying degrees of effect on various tissues and organs in the body, with the most serious side effects being respiratory depression and gastrointestinal depression 8 – 10 . It has also been demonstrated that diacetylmorphine can cause abnormal electrocardiographic parameters 11 ; however, little is known about the mechanisms by which diacetylmorphine causes myocardial rhythm abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Entre seus efeitos adversos, o principal é a dificuldade respiratória, que pode ser fatal. A literatura ainda descreve outras complicações, como choque, lesão miocárdica, edema pulmonar, lesão renal aguda, rabdomiólise e leucoencefalopatia(YILDIRIM et al, 2020). Para evitar tais eventos a longo prazo, opta-se por utilizar…”
unclassified